PERFORMANCE MEASUREMENT IN ENTREPRENEURSHIP EDUCATION: TARGET AS A KEY TO SUCCESS OF BUSINESS RUN BY STUDENTS - Wijaya, Oscarius Yudhi Ari; Radianto, Wirawan ED (Universitas Brawijaya, Indonesia, 2017)
Entrepreneurship education has more varied teaching methods than other teaching methods in education. One of the most commonly used teaching methods is experiential- based learning. Through this method, students experience entrepreneurship education through their experience of establishing real business projects. One important aspect of this method is the target given to students. Target is one of the most frequently used aspects of management control mechanism, especially performance measurement. This study aims to investigate in-depth how students as businessmen interpret target charged to them. Qualitative approach with descriptive phenomenology method is used in this study. Interview is used as the primary data collection method. This study found that target is interpreted in such a way by the students. In this study, it is found that target is positively interpreted by students, but there are some students interpret target negatively. There is one key that arises in the interpretation; target is the key to the success of the business project run by students because target can increase student's motivation in running business project.